2023
DOI: 10.1097/mpg.0000000000003784
|View full text |Cite
|
Sign up to set email alerts
|

Catch-Up Growth in Infants and Young Children With Faltering Growth: Expert Opinion to Guide General Clinicians

Abstract: Sources of Funding: This article was supported by a grant from Danone to enable a consensus meeting to be held virtually on May 2021 and to facilitate the writing and editing of the manuscript. The funders made no scientific, writing, or editorial contribution to the meeting or manuscript. O.G. has given lectures or attended advisory boards for Danone, Biocodex, and Fresenius Kabi. K.H. has received honoraria from Nestle Nutrition Institute and participated as advisory board member for Danone. A.V.K. has recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Finally, proxy body-composition indices with arm anthropometry also showed that arm muscle indices, but not arm fat indices, were larger in the ONS + DC group compared with the control group. Together, these observations do not suggest continuous and disproportionate weight gain but show improvements in height and body composition assessments ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, proxy body-composition indices with arm anthropometry also showed that arm muscle indices, but not arm fat indices, were larger in the ONS + DC group compared with the control group. Together, these observations do not suggest continuous and disproportionate weight gain but show improvements in height and body composition assessments ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…A positive change in HAD has been interpreted as a faster-than-normal growth velocity compared to children of their age and sex ( 36 , 46 , 56 , 57 ), which fulfills one criterion of catch-up growth ( 46 , 47 ). Although a wide variety of ‘catch-up growth’ definitions have been used earlier ( 37 , 58 ), Frongillo et al have recently specified the criteria necessary to demonstrate catch-up growth ( 47 ). These criteria are: an initially reduced growth velocity, the removal of an inhibiting condition, and a subsequent higher-than-normal growth velocity ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Bayesian geostatistical analysis done in Ethiopia found that wealth status as a significant predictor of stunting among under-five children [ 13 ]. The underlying reasons for the increased prevalence of growth failure in children from low-income households can be attributed to insufficient food intake, a higher likelihood of illness, and limited access to essential healthcare services [ 58 , 59 ]. It is widely acknowledged that children from low-income households are at a greater risk of growth failure due to inadequate nutrition, which has a direct impact on their overall development and well-being.…”
Section: Discussionmentioning
confidence: 99%